PENGEMBANGAN SISTEM E-COMMERCE PAGUYUBAN USAHA KECIL DAN MENENGAH KARYA MANDIRI DI TEGAL - Ridwan Suhud; M. Yudhi Rezaldi (Pusbindiklat - LIPI, 2014)
Development of e-commerce systems of Society of Small and Medium Enterprises (SMEs) Karya Mandiri is one of main activities of the program implementation on utilization of science and technology in Pesarean Village, Adiwerna District, Tegal Regency, which aims to improve the competitiveness of SMEs in order to promote, market and sell products of metal crafts, such as agricultural equipment, construction, household appliances and motor vehicle accessories to internet users without limited space and time through the website. Development of SMEs e- commerce systems uses methods of software development life cycle consisting of analysis and definition for system requirements, system and software design, implementation and unit testing, integration and system testing, also operation and maintenance. In the current research, SMEs e-commerce system was developed based on an open source software that is using the programming language PHP version 5.4.3 and html, My SQL database server versions 5.5.24, and Apache version 2.2.22. Result of the development of e-commerce systems is in form of SMEs e-commerce website Karya Mandiri which can be accessed through the Internet.